Simultaneous inhibition of aryl hydrocarbon receptor (AhR) and Src abolishes androgen receptor signaling - Ghotbaddini, Maryam; Cisse, Keyana; Carey, Alexis; Powell, Joann B. (PLOS ONE, 2017)
Altered c-Src activity has been strongly implicated in the development, growth, progression, and metastasis of human cancers including prostate cancer. Src is known to regulate several biological functions of tumor cells, including proliferation. There are several Src inhibitors under evaluation for clinical effectiveness but have shown little activity in monotherapy trials of solid tumors. Combination studies are being explored by in vitro analysis and in clinical trials. Here we investigate the effect of simultaneous inhibition of the aryl hydrocarbon receptor (AhR) and Src on androgen receptor (AR) signaling in prostate cancer cells. AhR has also been reported to interact with the Src signaling pathway during prostate development. c-Src protein kinase is associated with the AhR complex in the cytosol and upon ligand binding to AhR, c-Src is activated and released from the complex. AhR has also been shown to regulate AR signaling which remains functionally important in the development and progression of prostate cancer. We provide evidence that co-inhibition of AhR and Src abolish AR activity. Evaluation of total protein and cellular fractions revealed decreased pAR expression and AR nuclear localization. Assays utilizing an androgen responsive element (ARE) and qRT-PCR analysis of AR genes revealed decreased AR promoter activity and transcriptional activity in the presence of both AhR and Src inhibitors. Furthermore, co-inhibition of AhR and Src reduced the growth of prostate cancer cells compared to individual treatments. Several studies have revealed that AhR and Src individually inhibit cellular proliferation. However, this study is the first to suggest simultaneous inhibition of AhR and Src to inhibit AR signaling and prostate cancer cell growth.